2020
DOI: 10.48550/arxiv.2012.09068
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Equilibration of the Quark-Gluon Plasma at finite net-baryon density in QCD kinetic theory

Xiaojian Du,
Sören Schlichting

Abstract: We explore the out-of-equilibrium dynamics of the Quark-Gluon Plasma at zero and finite netbaryon density based on an effective kinetic theory of Quantum Chromo Dynamics (QCD). By investigating the isotropization of the longitudinal pressure, we determine the relevant time and temperature scales for the onset of viscous hydrodynamics, and quantify the dependence on the chemical composition of the QGP. By extrapolating our results to realistic coupling strength, we discuss phenomenological consequences regardin… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…Despite the loss of thermal equilibrium, different microscopic simulations have shown that the evolution of the energy density and of the longitudinal pressure are fairly universal when expressed as a function of the dimensionless scaling variable [19,24] 14) and ( 15), as a function of w calculated in weak coupling regime with QCD kinetics [15,14]. Dashed lines correspond to the asymptotic behavior in (first order) viscous relativistic hydrodynamics.…”
Section: Dilepton Production In a Non-equilibrium Qgpmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the loss of thermal equilibrium, different microscopic simulations have shown that the evolution of the energy density and of the longitudinal pressure are fairly universal when expressed as a function of the dimensionless scaling variable [19,24] 14) and ( 15), as a function of w calculated in weak coupling regime with QCD kinetics [15,14]. Dashed lines correspond to the asymptotic behavior in (first order) viscous relativistic hydrodynamics.…”
Section: Dilepton Production In a Non-equilibrium Qgpmentioning
confidence: 99%
“…With regards to describing the production of electromagnetic probes during the pre-equilibrium stage, two important effects must be taken into account. First of all, the initial stage is expected to be highly gluon dominated [11], and it takes time for quarks and antiquarks to be produced and reach thermal abundances [12,13,14,15]. Secondly, due to the rapid longitudinal expansion, the momentum distribution of quarks is strongly anisotropic at early times [8], with the typical transverse momenta larger than longitudinal momenta.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, weak-coupling methods are available for generic theories and have also been widely studied. The first works studying thermalization of pure Yang-Mills theory from simple initial conditions [18] have been extended to * smi6nd@virginia.edu Quantum Chromodynamics (QCD) [19][20][21][22] and calculations based on this physical picture have been extended to describe systems of enough complexity to be used in realistic phenomenological modelling of heavy-ion collisions [23,24] and even in light-ion collisions [25]. This picture has also been applied to parametric estimates of thermalization times during reheating [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…1 Kinetic theory can act as an effective description of processes in weakly-coupled quantum field theories when interference effects can be neglected [17,18]. In particular, the effective kinetic theory of QCD [19][20][21] has recently become a framework of significant theoretical and phenomenological interest in the context of ultrarelativistic heavy-ion collisions [22][23][24][25][26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%